Induction of Interleukin-1β by Human Immunodeficiency Virus-1 Viral Proteins Leads to Increased Levels of Neuronal Ferritin Heavy Chain, Synaptic Injury, and Deficits in Flexible Attention - Festa, Lindsay (J Neurosci, 2015)
Synaptodendritic pruning and alterations in neurotransmission are the main underlying causes of HIV-associated neurocognitive disorders (HAND). Our studies in humans and nonhuman primates indicated that the protein ferritin heavy chain (FHC) is a critical player in neuronal changes and ensuing cognitive deficit observed in these patients. Here we focus on the effect of HIV proteins and inflammatory cytokines implicated in HAND on neuronal FHC levels, dendritic changes, and neurocognitive behavior. In two well characterized models of HAND (HIV transgenic and gp120-treated rats), we report reductions in spine density and dendritic branches in prefrontal cortex pyramidal neurons compared with age-matched controls. FHC brain levels are elevated in these animals, which also show deficits in reversal learning. Moreover, IL-1β, TNF-α, and HIV gp120 upregulate FHC in rat cortical neurons. However, although the inflammatory cytokines directly altered neuronal FHC, gp120 only caused significant FHC upregulation in neuronal/glial cocultures, suggesting that glia are necessary for sustained elevation of neuronal FHC by the viral protein. Although the envelope protein induced secretion of IL-1β and TNF-α in cocultures, TNF-α blockade did not affect gp120-mediated induction of FHC. Conversely, studies with an IL-1β neutralizing antibody or specific IL-1 receptor antagonist revealed the primary involvement of IL-1β in gp120-induced FHC changes. Furthermore, silencing of neuronal FHC abrogates the effect of gp120 on spines, and spine density correlates negatively with FHC levels or cognitive deficit. These results demonstrate that viral and host components of HIV infection increase brain expression of FHC, leading to cellular and functional changes, and point to IL-1β-targeted strategies for prevention of these alterations. SIGNIFICANCE STATEMENT This work demonstrates the key role of the cytokine IL-1β in the regulation of a novel intracellular mediator [i.e., the protein ferritin heavy chain (FHC)] of HIV-induced dendritic damage and the resulting neurocognitive impairment. This is also the first study that systematically investigates dendritic damage in layer II/III prefrontal cortex neurons of two different non-infectious models of HIV-associated neurocognitive disorders (HAND) and reveals a precise correlation of these structural changes with specific biochemical and functional alterations also reported in HIV patients. Overall, these data suggest that targeting the IL-1β-dependent FHC increase may represent a valid strategy for neuroprotective adjuvant therapies in HAND.